Experience and views of nurses on nursing services andpersonal protective equipment in Covid-19 pandemic the caseof Turkey: A cross-sectional study - ÇELİK, YUSUF (My University, 2022)
Background: During the COVID-19 pandemic, there were difficulties in planning the nursing workforce and personal protective equipment. Aim: The purpose of this study was to identify the experiences and views of nurses on personal protective equipment use and nursing workforce planning in Turkey. Methods: This descriptive and cross-sectional study was conducted between 23 December 2020 and 3 May 2021, among 362 nurses who agreed to participate in this study voluntarily. Results: The findings showed that the satisfaction scores were significantly higher for those nurses who worked in 8-h shifts, were not assigned to different clinics, were notified by an official letter and 1 week or month in advance before assignment compared with nurses in other categories. Conclusions: The problems that have arisen in the COVID-19 pandemic process have made it clear that there is a need for a nursing services management model in the event of an epidemic. Implications for Nursing Management: This study reveals the need for the ‘Nursing Services Management Model in the Event of an Epidemic’ by discussing the problems of nurse workforce planning and protective personal equipment management from the perspective of nurses who experienced these problems at first hand. KEYWORDS COVID-19, nurses, nursing management, personal protective equipment
Keywords: Sağlık Bilimleri; Sosyal ve Beşeri Bilimler; Health Sciences; Social Sciences and Humanities; Klinik Tıp (MED); Sosyal Bilimler (SOC); Clinical Medicine (MED); Social Sciences (SOC); COVID-19; nurses; nursing management; personal protective equipment